Pengaruh Kepuasan Wajib Pajak, Kepatuhan Wajib Pajak dan Kualitas Pelayanan Petugas Pajak Terhadap Penerimaan Pajak: Studi Kasus di Kantor Samsat Kota Bengkulu Tahun 2024 - Emya Pepayosa Br Karo; Winny Lian Seventeen; Fathul Hilal Perdanakusuma (Economic Reviews Journal, 2024)
The aim of this research is to determine the effect of taxpayer satisfaction, taxpayer compliance and the quality of tax officer services on tax revenues (case study at the Bengkulu City Samsat office in 2024). The analytical tools used in this research are quantitative analysis (Validity and Reliability Test), multicollinearity analysis, multiple linear regression, partial test (t test), simultaneous test (f test) and coefficient of determination. The method used in this research is a quantitative method and an association survey with a quantitative approach. The population that the researchers will use is 233,164 vehicle taxpayers at the Bengkulu City Samsat office in 2024. The sampling technique used in this research is the purposive sampling method. The sample taken in this research was 100 taxpayers at the Bengkulu City Samsat office. Data collection techniques use questionnaires or questionnaires with a Likert scale. The analytical method used in this research is multiple linear regression analysis and hypotheses using the t test and f test. Simultaneously, the influence of taxpayer satisfaction, taxpayer compliance and tax service quality has a significant effect with an f count of 6,690 on tax revenues. Partially, it shows that the influence of taxpayer satisfaction, taxpayer compliance has a significant effect on tax revenue, while the quality of tax officer service does not have a significant effect on tax revenue.